2016
DOI: 10.1007/s10611-016-9610-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of petty corruption on firm innovation in Vietnam

Abstract: More specifically, informal payments by Vietnam firms are shown to encourage overall innovation, product improvement innovation and new innovation. This is not entirely unexpected, in view of other findings reported in this special issue, and in view of the business practice of paying small informal fees to speed up transactions with the public sector in Vietnam. However, the findings also strongly implies that in the fight against corruption it is critically important to highlight (to firms) the true costs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 38 publications
1
50
2
Order By: Relevance
“…Xia et al, (2018) in their survey developed in the context of China, found a significant positive impact of corruption into innovation. Similarly, the same finding is confirmed in another study developed in Vietnam, thus supporting the "greasing the wheel" thesis (Nguyen et al, 2016). A recent study uncovered that political corruption benefits firms in most of their innovative activities (Riaz and Cantner, 2020).…”
supporting
confidence: 69%
“…Xia et al, (2018) in their survey developed in the context of China, found a significant positive impact of corruption into innovation. Similarly, the same finding is confirmed in another study developed in Vietnam, thus supporting the "greasing the wheel" thesis (Nguyen et al, 2016). A recent study uncovered that political corruption benefits firms in most of their innovative activities (Riaz and Cantner, 2020).…”
supporting
confidence: 69%
“…So, the corruption has a negative impact on the expectation that a company will be innovative and at the same time, it has a positive impact in overcoming the inefficient structures and institutions. Ngoc et al (2016) have studied the impact of corruption depending on its size, making a clear distinction between "the petty corruption" and "the grand corruption". In their view, "the petty corruption" may have a positive effect on business innovation, allowing getting immediate benefits for the company, especially when it comes to overcoming the inefficient structures that hinder the company's activity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite improvement over the past years, corruption is still considered widespread throughout the country, and Vietnam still lags behind other Asian countries regarding corruption control and most governance indicators (Transparency International, 2012). International studies suggest that corruption affects the business environment both positively and negatively (e.g., Dang, 2016;Méon & Weill, 2010;Nguyen, Doan, Nguyen, & Tran-Nam, 2016;Welter & Smallbone, 2014). However, relatively little literature has been published on corruption in Vietnam, especially with respect to its effect on the business environment.…”
Section: Introductionmentioning
confidence: 99%